Prevalência da diabetes mellitus tipo 1 em Portugal, 1995-1999 coorte de jovens do sexo masculino. - Z Jorge; E Lacerda Nobre; A Macedo; J Jácome De Castro (Acta Médica Portuguesa, 2003)
We designed a study to assess the prevalence of type 1 diabetes mellitus among the Portuguese population. The study was based on a cohort of young Portuguese men inspected at the different recruitment Centres of the Portuguese Armed Forces in 1995 and 1999. We found a prevalence of 1.28 and 1.58 cases per 1,000 young men aged 20 (median), in 1995 and 1999, respectively. As far as the geographical distribution of this population was concerned, the recruitment centres (RC) with highest prevalence of diabetes in 1995 were that of Oporto, Évora and Lisboa. In 1999, highest prevalence was in Évora, Faro and Lisbon. The greatest increase was found at the RCs in Faro, Évora and Vila Real. Although the regional asymmetries are not very significant, they point to a higher prevalence in the southern region and in the urban areas of Lisbon and Oporto.